ANALYSIS OF VEHICLE LOADING AND UNLOADING OPERATIONS AT THE VEHICLE YARD OF THE INTERNATIONAL TERMINAL AT TANJUNG PRIOK PORT IN RESPONSE TO THE SURGE IN VEHICLE VOLUME - Ahmad Zulfadilah; Ulfah; Rut Handayani; Ramadhani Nur Saputra (Universitas Udayana, 2025)
The vehicle terminal is a special port for loading and unloading vehicles in the form of Completely Built Up (CBU), Trucks, Heavy Tractors, and spare parts. In Indonesia, there is the second largest vehicle terminal gate in Southeast Asia, namely the Tanjung Priok Vehicle Terminal. The export of Indonesian vehicles through Tanjung Priok reached its highest point in 2018, amounting to 264,533 units. Meanwhile, the vehicle import policy in Indonesia is not supported by building a manufacturing center which will reduce the country's dependence on car imports. So it is necessary to analyze the height of the accumulation field of the Tanjung Priok Port International Vehicle Terminal in order to meet the increasing number of vehicles. In this research, it examines the risk of vehicle terminal buildup field and vehicle terminal operation management authority in order to reduce the number of piling field requirements. The data analysis of the stacking field uses a multivariate regression model to review the predicted increase in the number of vehicles until 2030. Meanwhile, the frequency analysis uses the monte carlo simulation to obtain a more effective time duration in vehicle terminal management. The results of the accumulation of field data analysis for important criteria are still sufficient. Meanwhile, the criteria for export and total criteria are not sufficient for 2026 and 2030, respectively. The results of the analysis show that the change in the area of the dumpsite is smaller due to the effectiveness of terminal vehicle management time.